2013
DOI: 10.1007/s11273-013-9327-1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial decision support system for assessing lake pollution hazard: southeastern pampean shallow lakes (Argentina) as a case study

Abstract: This study gives an account of the implementation of a decision support system as a logical framework for assessing lake pollution hazard. The use of this system is demonstrated with an example from two lake watersheds, each one with different land-use, soil and topographic characteristics and also management regulations for natural resource protection. Lake pollution hazard is assessed as a function of two primary topics: hydrologic and soil conditions. This model shows the state of each evaluated subwatershe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…As mentioned earlier, over the last years, La Brava and Los Padres lakes have been impacted by human disturbances, derived from agricultural and recreational activities, urbanization and waste increase from different origins (Romanelli et al, 2014). Several studies have confirmed the anthropogenic impact on the two lakes, showing the presence of diverse pollutants (heavy metals, pesticides and herbicides) in water, soil, aquatic macrophytes, and fauna (Miglioranza et al, 1998(Miglioranza et al, , 2004Romanelli et al, 2014).…”
Section: Discussionmentioning
confidence: 93%
“…As mentioned earlier, over the last years, La Brava and Los Padres lakes have been impacted by human disturbances, derived from agricultural and recreational activities, urbanization and waste increase from different origins (Romanelli et al, 2014). Several studies have confirmed the anthropogenic impact on the two lakes, showing the presence of diverse pollutants (heavy metals, pesticides and herbicides) in water, soil, aquatic macrophytes, and fauna (Miglioranza et al, 1998(Miglioranza et al, , 2004Romanelli et al, 2014).…”
Section: Discussionmentioning
confidence: 93%
“…In a 2.5 km-radius buffer from each lake, Romanelli et al, 2013 identified the dominance of agricultural activities in La Brava Lake (63.65 %), horticulture in Los Padres Lake (63.88 %; Horticultural Belt of Mar del Plata City with greenhouse and open-field cropping systems) and pastures with livestock in Nahuel Rucá Lake (44.15 %). Moreover, close to Los Padres and La Brava lakes there are two permanent villages (Los Padres and La Brava) with 1,672 and 115 permanent residents, respectively (INDEC, 2012), and many tourism-related facilities along their shores (Romanelli et al, 2014b). Nahuel Rucá Lake is located within two private farmlands with cattle-breeding as the dominant economic activity.…”
Section: Study Areamentioning
confidence: 99%
“…Groundwater is a significant water source to these three lakes, directly discharging into the lake bed and indirectly via the gaining inflow streams. In addition, in the case of La Brava Lake, it also receives a water contribution from the fissure system present in La Brava Range (western margin of the lake) (Romanelli et al, 2014b).…”
Section: Hydrochemical Datamentioning
confidence: 99%
“…The creek has a length of 30 km, and before its outfall it passes through horticultural areas and an urban zone along the north side of Mar del Plata city (Miglioranza et al, 2004). Both the lake and the creek are embedded in an intensive horticultural agroecosystem (Miglioranza et al, 2004;Romanelli et al, 2014). On the other hand, along its urban portion, the creek receives the discharge of drain storms, draining large areas of the city.…”
Section: The Streammentioning
confidence: 99%
“…Both Los Padres lake and the headwaters of La Tapera creek receive diverse pollutants from surrounding horticultural areas (Miglioranza et al, 2004;Romanelli et al, 2014), therefore a differential detrimental effect on parasites at urban sections should imply the input of other compounds. La Tapera stream is not connected with official sewage dumps, however, Isla et al (1998) reported high concentrations of faecal coliforms attributed to domestic residential inputs which could be sources for other kinds of chemicals.…”
Section: Tablementioning
confidence: 99%